OPTIMIZATION OF THE BLUSH ON STICK BASE AND PHYTOCHEMICAL SCREENING OF MELINJO FRUIT (Gnetum gnemon Linn) - Likrah, Vira Saphira; Suparningtyas, Juniza Firdha; Kuncoro, Hadi (PROSIDING SEMINAR KIMIA, 2023)
Red melinjo skin or Gnetum gnemon has the potential to be used as an alternative natural dye because it has an attractive color due to the presence of carotenoid anthocyanin pigments, a derivative of terpenoid compounds. Carotenoids can be used as natural dyes in blush stick preparations. Melinjo peel was extracted by maceration using 70% ethanol and citric acid and after that it was tested for phytochemical screening and extract characterization. The blush on stick base formulation consists of several components including carnauba wax, candelilla wax, talcum, oleum ricini, methyl paraben, BHT, tween 80. color and scent. The base of the blush stick preparation is quite stable, homogeneous, pH 3.8-4.7 (close to skin pH), in accordance with the criteria of SNI 16-479-1998, easy to apply with an even color, and very homogeneous formulation when applied to hands. Keywords: Red melinjo skin, Blush on stick, anthocyanin